2022
DOI: 10.1021/acs.nanolett.2c01999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Stabilization of Multiplet Supercurrents in Multiterminal Josephson Junctions

Abstract: The dynamical properties of multiterminal Josephson junctions (MT-JJs) have attracted interest, driven by the promise of new insights into synthetic topological phases of matter and Floquet states. This effort has culminated in the discovery of Cooper multiplets in which the splitting of a Cooper pair is enabled via a series of Andreev reflections that entangle four (or more) electrons. Here, we show that multiplet resonances can also emerge as a consequence of the three-terminal circuit model. The supercurren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 36 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…These three sets of MAR signatures can be understood as independent Andreev reflections between all three pairs of terminals. We also observe a signature of Cooper quartet transport 35 38 , 42 , indicated by a lower resistance feature along the line V 1 = − V 2 . The differential resistance maps can also be plotted as a function of V 1 , V 2 where the quartet signature is clearly visible along the V 1 = − V 2 diagonal (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
“…These three sets of MAR signatures can be understood as independent Andreev reflections between all three pairs of terminals. We also observe a signature of Cooper quartet transport 35 38 , 42 , indicated by a lower resistance feature along the line V 1 = − V 2 . The differential resistance maps can also be plotted as a function of V 1 , V 2 where the quartet signature is clearly visible along the V 1 = − V 2 diagonal (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Our devices are based on multiterminal Josephson junctions made in graphene. In the past few years, the multiterminal junctions have been realized in a variety of materials [36][37][38][39][40][41] and have even found a foothold as a solution to technological problems [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant band structure may display topological properties such as Weyl singularities [10,11]. While providing strong motivation for MTJJs have been experimentally explored in various materials platforms including graphene/MoRe [22][23][24] and InAs/Al [25][26][27][28][29]. These experiments focused on the gate and magnetic field dependence of the supercurrent flow between adjacent and nonadjacent superconducting terminals [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also reported signatures of quartet pairings [23,25,30], arising from crossed Andreev reflection processes. However, studies of threeterminal Josephson junctions [24] and a network of tunnel junctions [31] argue that the resonant features may also arise from circuit-network effects.…”
Section: Introductionmentioning
confidence: 99%